UREDITEME project - building capacities through FP7 research networking - Bairrão, R. (2014)
The paper refers to FP7 project for upgrading and renovation of research and personnel capacities of Institute of Earthquake Engineering and Engineering Seismology, IZIIS, Skopje, Macedonia. Protection of structures against strong seismic impact primarily depends on the quality of the applied standards for design and construction. The reinforcement of the IZIIS’ RTD capacities creates the conditions for knowledge delivering which should be built-in into the technical standards. To realize these strategic goals, scientific network was established with similar research institutions from the EU member states (LNEC-Portugal, ELSA-EU, and University of Bristol - UK). Exchange of knowledge and experience in the field of earthquake engineering and geotechnical engineering was successful story that open vast opportunities for further collaboration between UKIM-IZIIS and LNEC. This paper emphasis very positive experience gathered during the execution of the UREDITEME project.